PEMODELAN CAKUPAN IMUNISASI CAMPAK PADA ANAK USIA 12-59 BULAN DI PROVINSI ACEH TAHUN 2017 - Putu Rima Ayu Padini; Timbang Sirait (Politeknik Statistika STIS, 2020)
Measles is a highly contagious disease that can leads to serious complications. Measles can be effectively prevented by measles immunization. But, Indonesia still has not achieve the 95% target of measles immunization coverage in each district and nationally. Province with the lowest measles immunization coverage in Indonesia is Aceh with 70,8% of first dose coverage and 20,4% of second dose coverage in 2017. This means there are still many people with no protection against measles that can caused future outbreaks. Hence, this study aims to identify variables affecting measles immunization coverage among children aged 12-59 months in Aceh by using 2-level binary logistic regression. The result of this study shows that measles immunization coverage among children aged 12-59 months in Aceh is only 63,4%. Measles immunization coverage among children aged 12-59 months is affected by mother’s occupation, health insurance (BPJS Kesehatan), immunization card, high population density, and availability of health workers (health workers/1000 population). From this research, the government can improve measles immunization coverage by doing socialization about measles immunization in the village level (gampong) and improving quantity and quality of the health facilities and health workers, especially in highly-densed districts.